"From head to Toe" : A Lexical, Semantic, and Morphosyntactic Study of Idioms in Phraseological Dictionaries in English and Spanish (2020)
ABSTRACT: In recent times, interest in the study of phraseology in general and specialized lexicographic resources has increased (Castillo Carballo 2006, Aguado de Cea 2007, Mellado 2008, Buendía Castro & Faber 2015). However, to date, a lack of knowledge related to the characterization and indexation of phraseological units (PUs) in lexicographic resources remains. That issue is addressed here through an analysis of phraseological units in the entries of two phraseological dictionaries, one in Spanish, and one in English: the Diccionario fraseológico documentado del español actual (Seco, Andrés & Ramos 2004) and the Collins COBUILD Dictionary of Idioms (Sinclair & Moon 1997). To perform this analysis, two databases containing 21,045 entries extracted from the two dictionaries mentioned above were compiled. The databases were tagged syntactically and semantically in order to extract 816 morphosyntactic patterns, 2,655 combinations of semantic categories (Semantic patterns) and a series of lexical and lexicographic information about indexation of PUs in dictionaries.